Modelagem dos processos físico-químicos e atmosféricos envolvidos na formação de oxidantes fotoquímicos em megacidades: o caso da região metropolitana do Rio de Janeiro - Moraes, Nilton Oliveira (2017)
Presents an integrated computational system composed of a meteorological model, biogenic / anthropogenic emissions and air quality, implemented and adequate in a high performance computational platform, for the understanding of dynamic, thermodynamic and physico-chemical processes that impact on the formation of Photochemical oxidants in RMRJ. For better representativeness of the results, methodologies were developed that provided atmospheric emissions databases in high resolution. Statistical assessments of system performance were performed comparing with observed data from meteorological stations and the air quality monitoring network, and an investigation of atmospheric pollutant concentrations occurred in different meteorological conditions. The results are presented in digital maps on the geographic information system platform for an integrated environmental analysis.